The synergism between self-activated and impurity-related emissions of LiCa3ZnV3O12: lattice distortion, energy transfer and temperature sensing effect. Issue 55 (16th December 2022) - Li, Jie; Shi, Ruixia; Cao, Yongqiang; Ma, Qian; Chen, Ling; Zhang, Aiyu; Yang, Ping
Abstract : Combination of Eu 3+ -related and self-activating emissions of LCZV analyzed by crystal structure information, leading to potential applications as color-tunable phosphors, white light LED and luminescent temperature sensor. Abstract : Some of the metal vanadates have special self-activated luminescence. In order to further enrich its luminous color, luminescent impurity ions can be introduced into its lattice. The interaction between the self-activated emission and the impurity-related emission remains to be studied. In this work, the synergism between the two kinds of emission in LiCa3 ZnV3 O12 was explored from these three aspects: lattice distortion, energy transfer and temperature effect. Eu 3+ ions replace Ca 2+ ions in the lattice of LiCa3 ZnV3 O12, leading to a lattice contraction of the LCZV host, which depresses the self-activating emission around 500 nm. The characteristic linear emissions of Eu 3+ ions are also observed benefiting from the energy transfer from [VO4 ] 3− to Eu 3+ . Since the temperature quenching effect is more sensitive for the self-activated emission than that for the Eu 3+ -related ones, the phosphor can be applied as a luminescent temperature sensor, with the absolute and relative temperature sensitivities of 0.012 K −1 and 1.56% K −1, respectively.